Understanding of oxygen reduction reaction by examining carbon-oxygen gasification reaction and carbon active sites on metal and heteroatoms free carbon materials of different porosities and structures. (July 2019) - Gabe, Atsushi; Ruiz-Rosas, Ramiro; Morallón, Emilia; Cazorla-Amorós, Diego
Abstract: Knowledge of the carbon active sites for Oxygen Reduction Reaction (ORR) remains confusing and controversial and thus the detailed mechanism is still not clarified. Considering the nature of the carbon-oxygen interaction in active sites during the gasification reaction, it could be inferred that the sites for this reaction are the same as those participating in the ORR. Herein, the relationship between carbon-oxygen gasification properties and ORR activities was elucidated. Carbon materials including different structures and porosities were selected and extensively characterized in terms of structural and electrochemical properties. Regarding gasification properties, active surface area (ASA) and reactivity for carbon-oxygen reaction were determined. A good linear correlation is found between ORR activity and carbon-oxygen gasification reactivity. Interestingly, similar correlation is found between ORR activity or gasification reactivity and ASA, although two different slopes are observed for the analyzed samples, being higher for the carbon nanotubes (CNT) based samples. The results suggest that the active sites participating in the gasification reaction can be catalytic sites for ORR although the specific catalytic activity is determined by the carbon structure. Thus, active sites in CNT show higher activities toward ORR and carbon gasification reactivities than others. Graphical abstract: Image 1